The Relativity of Moral Virtue in Aristotle’s Ethics - Focusing on His Doctrine of the Mean - 김도형 (윤리연구, 1(122), 2018)
According to Aristotle, morally virtuous person chooses and practices ‘what is mean’ well amongst actions and affections. It seems that the action(praxis) and affection(pathos) chosen and practiced by a person of morally virtuous character are what he means by the expression ‘the mean relative to us’(to meson pros hēmas). (EN2.6, 1106b14) Therefore, it is necessary to know what this expression means in order for our better understanding on not only virtuous actions and affections, but also moral virtue, the character which makes such actions and affections possible. However, this expression often causes a controversy, because the sense of ‘us’(hēmas) in it is somewhat ambiguous. As a matter of fact, it is more than grasping the meaning of that simple word that we try to figure out what it means. The word ‘us’ in ‘the mean relative to us’ can be a standard according to which we judge the mean options amongst various actions and affections. That is, it can be said, Aristotle explains to which standard moral actions and affections are relative by the word ‘us’. If so, it is very important to figure out the sense of ‘us’ in that we are able to see what his idea is on some kind of moral standard by which we can judge what is good or not and thereby to understand what he would say about the relativity of moral virtue, if any. In this paper, we will first introduce a ‘character-relativity’ position that claims morally good actions and affections are according to the character of each agent. We will, then, criticize why this position is problematic and argue for a ‘circumstance-relativity’ position that the mean actions and affections are not to be judged or chosen by the agent’s character, but by the circumstance where the agent is. Furthermore, it will be argued, as long as the relativity of the mean is confined to the circumstance, ‘moral virtue’ is, as well, relative in the sense that morally good actions and affections can be decided according to the circumstance given. KCI Citation Count: 0